1988
DOI: 10.1007/bf00165627
|View full text |Cite
|
Sign up to set email alerts
|

Transmitter release patterns of noradrenergic, dopaminergic and cholinergic axons in rabbit brain slices during short pulse trains, and the operation of presynaptic autoreceptors

Abstract: Slices of rabbit brain were field-stimulated either by single electrical pulses or by trains of 4 or 8 pulses at 1 or 100 Hz in order to study transmitter release patterns and the autoinhibition of transmitter release. The slices were preincubated with 3H-noradrenaline (cortex), 3H-dopamine (caudate nucleus) or 3H-choline (caudate nucleus). Slices preincubated with 3H-noradrenaline were superfused with medium containing desipramine 1 mumol/l. The overflow of tritium elicited by single pulses amounted to 0.19% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…This well-documented effect is due to blockade of autoreceptors receptors that normally inhibit release when activated by dopamine (Starke, 1989). The short duration of the pl P (30 msec) gives insufficient time for dopamine autoreceptors to function between pulses (Mayer et al, 1988;Singer, 1988 transmission at the neuromuscular junction differ greatly in that the dopamine released into the synaptic cleft seems destined for extrasynaptic space.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This well-documented effect is due to blockade of autoreceptors receptors that normally inhibit release when activated by dopamine (Starke, 1989). The short duration of the pl P (30 msec) gives insufficient time for dopamine autoreceptors to function between pulses (Mayer et al, 1988;Singer, 1988 transmission at the neuromuscular junction differ greatly in that the dopamine released into the synaptic cleft seems destined for extrasynaptic space.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the uptake transporter, the rapid binding rate calculated above and the absence of effect of uptake inhibitors on dopamine efflux lead us to predict that a significant fraction of the uptake sites are extrasynaptic as is found in cultured fetal dopamine neurons (Cerrutti et al, 1991). Since the complete development of dopamine autoreceptor inhibition occurs in the 40-100 msec range (Mayer et al, 1988;Singer, 1988;Kennedy et al, 1992) which indicates that autoreceptors have sufficiently fast binding kinetics to buffer efflux from the synaptic cleft, the failure to alter dopamine efflux with a D, antagonist also suggests an extrasynaptic location for dopamine autoreceptors. Indeed, recent anatomical evidence supports an extrasynaptic location for some D, receptors in the rat striatum (Levey et al, 1993;Sesack et al, 1994).…”
Section: Concentrations Of Dopamine In the Synaptic Cleft And Extrasymentioning
confidence: 99%
See 1 more Smart Citation
“…However, a train of pulses is necessary to obtain measurable amounts of [DA] o from somatodendritic regions in this system . Short high-frequency trains, or "pseudo-one pulse" stimulations (Յ 100 msec; see also Palij and Stamford, 1993), offer a compromise to a single pulse whereby high transmitter efflux is evoked but in a period of time too short to activate the DA autoreceptor (Mayer et al, 1988;Singer, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…Due to its anticholinesterase activity, tacrine should increase the extracellular concen tration of acetylcholine (ACh), like other cholinesterase inhibitors. It has been found that an increase in the ex tracellular concentration of ACh, or application of mus carinic agonists, inhibits ACh release from the nerve ter minal (11,12). Previous researchers have reported that tacrine inhibits depolarization-induced ACh release (13,14), although these observations would be against the clinical usefulness of tacrine.…”
mentioning
confidence: 99%